2021
DOI: 10.1177/0956797621993109
|View full text |Cite
|
Sign up to set email alerts
|

Do Diversity Awards Discourage Applicants From Marginalized Groups From Pursuing More Lucrative Opportunities?

Abstract: Four studies reveal that offering diversity awards (i.e., awards for applicants from marginalized groups) has unintentionally negative implications for equity. Across the four studies, applicants from marginalized groups were more likely to select the more lucrative award when two unrestricted awards were offered (Study 1: adults from racial groups underrepresented in U.S. colleges who were recruited from Amazon Mechanical Turk, N = 168; Studies 2–4: college women, N range = 152–628). However, the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Thus, graduate psychology programmes need to advocate to higher level bodies within their institutions to ensure that admissions scholarship structures also support diversification efforts. Additionally, BIPOC scholarships may discourage students from applying for more financially beneficial awards, particularly if the awards cannot be held in unison (Germano et al, 2021). Combined funding structures to promote diversity within research already exist in some places.…”
Section: Discussion: Potential Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, graduate psychology programmes need to advocate to higher level bodies within their institutions to ensure that admissions scholarship structures also support diversification efforts. Additionally, BIPOC scholarships may discourage students from applying for more financially beneficial awards, particularly if the awards cannot be held in unison (Germano et al, 2021). Combined funding structures to promote diversity within research already exist in some places.…”
Section: Discussion: Potential Solutionsmentioning
confidence: 99%
“…Because this scholarship is added to the general OGS, laureates do not have to choose between a larger, unrestricted reward and a smaller diversity award. Research findings demonstrate that students tend to pick the smaller diversity award in part because they perceive a better fit and a higher likelihood of success compared to unrestricted reward even when the number of awardees is equal (Germano et al, 2021). Psychology programmes, professors, and researchers—particularly those involved with policy and decision-making bodies—need to advocate for changes in funding structures, procedures, and policies to improve BIPOC equity.…”
Section: Discussion: Potential Solutionsmentioning
confidence: 99%
“…Namely, they may give the illusion of equitable candidate selection, but in actuality, convey the dual message that diversity awards are for applicants from marginalized racial/ethnic groups, whereas unrestricted awards (e.g., no eligibility criteria based on race/ethnicity) are for applicants from dominant cultural groups. Germano and colleagues ( 2021 ) found that, when presented with both diversity and unrestricted awards, applicants from marginalized racial/ethnic groups were more likely to prioritize submitting to diversity awards over unrestricted awards, even when the monetary prize was less. This limits the diversity of the applicant pool for awards that are often more prestigious and lucrative, and contributes to unrestricted awards being disproportionately awarded to White individuals (Germano et al, 2021 ).…”
Section: Leadership: Accountability To the Recruitment Retention And ...mentioning
confidence: 99%
“…Germano and colleagues ( 2021 ) found that, when presented with both diversity and unrestricted awards, applicants from marginalized racial/ethnic groups were more likely to prioritize submitting to diversity awards over unrestricted awards, even when the monetary prize was less. This limits the diversity of the applicant pool for awards that are often more prestigious and lucrative, and contributes to unrestricted awards being disproportionately awarded to White individuals (Germano et al, 2021 ). Rather than eliminating diversity awards, increase the financial value of diversity awards, and/or update the purpose and criteria of unrestricted awards to emphasize cultural diversity (Germano et al, 2021 ).…”
Section: Leadership: Accountability To the Recruitment Retention And ...mentioning
confidence: 99%
See 1 more Smart Citation